Fluency profiles in L2 monologue production: the role of underlying cognitive factors - Olkkonen, Sanna; Mutta, Maarit; Lintunen, Pekka. (Finland, 2025)
This article examines the role of cognitive fluency and different fluency profiles that underlie L2 speech fluency, in relation to cognitive efficiency in L1 and L2, in a group (n = 64) of university students of English. The participants conducted, first, a freely produced monologue narration task in L1 and L2. Second, they performed two cognitive tasks in L1 and L2 measuring the efficiency of lexical access: a rapid word naming task and a Stroop task. Thirdly, L2 proficiency level was assessed with a vocabulary test. The correlations between proficiency and cognitive variables were low to moderate. Based on a cluster analysis, the participants were divided into four fluency profile groups differing in speech and disfluency rate, proficiency, and efficiency of processing. The results suggest that an awareness that learners represent various fluency profiles based on cognitive variables can aid formal teaching situations to include more versatile tasks for different kinds of learners.